1875 Ga. Laws 189, An Act to Prevent the Shooting or Firing of Guns or Pistols in the Village of Vineville, in the County of Bibb, ch. 181, § 1 - (:unkn) unknown (General Publisher, 1875)
Prohibited the discharge, firing, shooting of any gun or pistol within three hundred yards of any public road through the village of Vineville.
--
Keywords: DISCHARGE